2021
DOI: 10.3390/catal11030356
|View full text |Cite
|
Sign up to set email alerts
|

Polyoxometalate Dicationic Ionic Liquids as Catalyst for Extractive Coupled Catalytic Oxidative Desulfurization

Abstract: Wettability is an important factor affecting the performance of catalytic oxidative desulfurization. In order to develop an efficient catalyst for the extractive coupled catalytic oxidative desulfurization (ECODS) of fuel oil by H2O2 and acetonitrile, a novel family of imidazole-based polyoxometalate dicationic ionic liquids (POM-DILs) [Cn(MIM)2]PW12O40 (n = 2,4,6) was synthesized by modifying phosphotungstic acid (H3PW12O40) with double imidazole ionic liquid. These kinds of catalysts have good dispersity in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 50 publications
0
24
1
Order By: Relevance
“…The chemical shifts of four supported catalysts with different loadings are as follows: 3% [C 2 IJMIM) 2 ]PW 12 O 40 /g-C 3 N 4 : δ = 3.34 (s, 6H, N-CH 3 ), 2.47 (s, H, C-H); 10% [C 2 IJMIM) 2 ]PW 12 O 40 /g-C 3 N 4 : δ = 3.34 (s, 6H, N-CH 3 ), 2.51 (s, H, C-H); 30% [C 2 IJMIM) 2 ]PW 12 O 40 /g-C 3 N 4 : δ = 3.34 (s, 6H, N-CH 3 ), 2.51 (s, H, C-H); and 50% [C 2 IJMIM) 2 ]PW 12 O 40 /g-C 3 N 4 : δ = 3.34 (s, 6H, N-CH 3 ), 2.51 (s, H, C-H). Compared with the results of the 1 H NMR analysis of [C 2 IJMIM) 2 ]PW 12 O 40 in our previous study,27 it was found that only hydrogen in two chemical environments was detected in the 1 H NMR spectra of the supported catalysts, which respectively corresponded to the hydrogen in the nitromethyl group on the imidazole ring of the catalyst and the hydrogen on the adjacent carbon. Moreover, the chemical shifts shift to high field.…”
contrasting
confidence: 47%
See 1 more Smart Citation
“…The chemical shifts of four supported catalysts with different loadings are as follows: 3% [C 2 IJMIM) 2 ]PW 12 O 40 /g-C 3 N 4 : δ = 3.34 (s, 6H, N-CH 3 ), 2.47 (s, H, C-H); 10% [C 2 IJMIM) 2 ]PW 12 O 40 /g-C 3 N 4 : δ = 3.34 (s, 6H, N-CH 3 ), 2.51 (s, H, C-H); 30% [C 2 IJMIM) 2 ]PW 12 O 40 /g-C 3 N 4 : δ = 3.34 (s, 6H, N-CH 3 ), 2.51 (s, H, C-H); and 50% [C 2 IJMIM) 2 ]PW 12 O 40 /g-C 3 N 4 : δ = 3.34 (s, 6H, N-CH 3 ), 2.51 (s, H, C-H). Compared with the results of the 1 H NMR analysis of [C 2 IJMIM) 2 ]PW 12 O 40 in our previous study,27 it was found that only hydrogen in two chemical environments was detected in the 1 H NMR spectra of the supported catalysts, which respectively corresponded to the hydrogen in the nitromethyl group on the imidazole ring of the catalyst and the hydrogen on the adjacent carbon. Moreover, the chemical shifts shift to high field.…”
contrasting
confidence: 47%
“…Dicationic ionic liquids (DILs) have attracted much attention in the ODS process due to their large cationic structure and high stability. [23][24][25][26] In our previous research, 27,28 Due to its unique graphite-like layered stacking structure and sp 2 hybrid π-conjugated electron band structure, g-C 3 N 4 has many excellent physical and chemical properties. 29 Moreover, it is simple in preparation, cheap in raw materials, and non-toxic and has good thermal and chemical stabilities.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, many researchers adopted the approaches of multi-stage extraction or extraction coupled with oxidation to perform desulfurization and obtained great results. [48][49][50][51]…”
Section: Inuence Of the Des/oil Volume Ratio On The Desulfurization Efficiencymentioning
confidence: 99%
“…Li et al carried out the oxidative desulfurization of fuel oil for the removal of dibenzothiophene by using imidazole-based polyoxometalate dicationic ionic liquids. Three kinds of catalyst were synthesized and tested under different conditions [8]. The catalytic performance of the catalysts was studied under different conditions by removing the dibenzothiophene from model oil.…”
Section: Special Issuementioning
confidence: 99%